A study on the strength improvement of local clayey soil using powdered eggshells - Nuada, Dexter L.; Vizconde, Vic Angelo G.
The most common problem of soil, especially clay soil, encountered in the field is its poor strength. And in order to address this, soil stabilization using commercially available additives have been used. However, these additives are expensive and cheaper alternatives are a welcome sight. Thus, the study aims to know the effect of eggshell powder to the compressive strength of clayey soil. Eggshell powder, in increments of 2.5% dry weight, was mixed with clayey soil from 0% to 10%. The maximum dry unit weights of the soil mixes were obtained by doing the Standard Proctor Test, using an optimum moisture content of 21.89%. Moreover, for the Unconfined Compression Test, soil mixes are prepared using an improvised rammer setup and moist-cured using hessian cloth for 7 and 28 days. Results of the Standard Proctor Test have shown an increasing trend in the dry unit weight with respect to increasing amount of eggshell. For the 28-day result, there is also an increasing trend behaviour versus eggshell content. However, the 7-day result did not show expected increase in the strength of the soil and the magnitude of the samples are higher than of those 28 days samples. No optimum eggshell powder content can been observed in the results because the trend behavior on both dry unit weight and unconfined compressive strength continues up to 10% eggshell powder content.